2017
DOI: 10.1111/jth.13637
|View full text |Cite
|
Sign up to set email alerts
|

Hematology journals do not sufficiently adhere to reporting guidelines: a systematic review

Abstract: Background Reporting guidelines and trial/review registration policies have been instituted in order to minimize bias and improve research practices. Objective The objective of this study was to investigate the policies of hematology journals concerning reporting guideline adoption and trial/review registration. Methods We performed a web-based data abstraction from the Instructions for Authors of 67 hematology journals catalogued in the Expanded Science Citation Index of the 2014 Journal Citation Reports to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Our findings, which highlight the suboptimal compliance with PRISMA and MOOSE guidelines, are in line with what has been previously demonstrated in other clinical areas of research. [17][18][19][20] These investigations have reported a compliance rate of as low as 50% with PRISMA and MOOSE guidelines among systematic reviews and metaanalyses, a finding that is consistent with our results despite the high-impact nature of our selected journals. We also observed that only a minority of the included metaanalyses reported the GRADE assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, which highlight the suboptimal compliance with PRISMA and MOOSE guidelines, are in line with what has been previously demonstrated in other clinical areas of research. [17][18][19][20] These investigations have reported a compliance rate of as low as 50% with PRISMA and MOOSE guidelines among systematic reviews and metaanalyses, a finding that is consistent with our results despite the high-impact nature of our selected journals. We also observed that only a minority of the included metaanalyses reported the GRADE assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Many journals across various medical subspecialties require adherence to reporting guidelines, but universal adoption has not yet been achieved. 7,[11][12][13][14][15] The literature suggests that if journals universally adopted reporting guidelines, the quality, transparency, and reproducibility of the published literature would strengthen. 8,[16][17][18][19][20] However, many addiction journals do not currently suggest or require reporting guidelines for submission.…”
mentioning
confidence: 99%
“…The evolution of journal endorsement of reporting guidelines and study registration in the last decade is depicted in figure 2 15–24. Our results showed that the journals we considered were more likely to endorse the CONSORT statement, the most commonly endorsed standard, and other reporting guidelines than journals in prior evaluations and covering other fields.…”
Section: Discussionmentioning
confidence: 79%